A second order phase transition characterized in the suppression of unlimited chaotic diffusion for a dissipative standard mapping - Miranda, Lucas Kenji Arima [UNESP]; Moratta, Raphael [UNESP]; Kuwana, Célia Mayumi [UNESP]; Yoshida, Makoto [UNESP]; de Oliveira, Juliano Antonio [UNESP]; Leonel, Edson Denis [UNESP] (Elsevier, 2022)
An order parameter is identified in a dissipative standard mapping during the transition from limited to unlimited chaotic diffusion. The suppression of the unlimited chaotic diffusion is proved due to the existence of a continuous phase transition. The average squared action is obtained, allowing the investigation of the main properties of the transition for long-time dynamics (stationary state). The main questions to characterize the order of this phase transition are: (i) what is the order parameter; (ii) what is the elementary excitation of the dynamics affecting the transport of particles in the system?
Keywords: Noise; Non-equilibrium; Nonlinear dynamics; Quantum processes